Energy Efficient Lighting System for Indoor Parking with Ubiquitous Communication. Issue 2 (May 2018) - Jha, Mahesh; Kumar, Navin
Abstract This paper presents visible light communication (VLC) based energy efficient lighting system in indoor parking area for illumination and at the same time would offer ubiquitous data communication. Light emitting diodes (LEDs) based VLC is used for communication and illumination at the same time. We have optimized the position of LED emitters on the ceiling in the parking area to obtain the desired signal-to-noise ratio (SNR) and bit error rate (BER). Two lighting configurations in the parking area are discussed. We compared the power transmission from LED emitters, number of emitters, SNR distribution, BER and cost for both the configurations. Multi-level pulse modulations are used in this work along with simple on off keying (OOK) for modulation. We compared OOK with M-PAM, multi-level pulse position modulation and invert multi-level pulse position modulation to obtain the required SNR and power to achieve the same BER. Simulation results are presented and discussed. It is observed that the system allows uniform illumination in the parking area and at the same time high data rate communication.